EDUKASI PENTINGNYA SELF DISCLOSURE REMAJA KEPADA ORANG TUA DENGAN MENGGUNAKAN MEDIA LEAFLET DI KELAS VIII E SMA NEGERI 11 KOTA JAMBI - Hera Wahyuni; Resiana Putri; Putri Putri; Nadia Yusrini; San Putri Istiqomah; Fara Ramadhani; Indah Kharisma (Labor Program Studi Pendidikan Sosiologi, 2023)
The goal of this activity is to educate the community, particularly teenagers and parents, on the importance of self-disclosure (self-disclosure) in adolescents. This community service activity took place on May 25, 2023, from 10 a.m. to 11 a.m. at State Senior High School 11 in Jambi City. This project took done in class VIII E, with 28 students participating. The strategy adopted in this community activity is leaflet media outreach about the necessity of teenage self-disclosure to parents. Analysis of the pre-test and post-test findings on teenage awareness of the value of self-disclosure (Self disclosure to Parents). This exercise makes use of up to 28 question sheets that are tailored to the socializing content. As a result, parents will have a better awareness of the value of self-disclosure, and their children will be more open to their parents. Self-disclosure entails providing numerous forms of information, ranging from little details to the most intimate and personal admissions.